2012
DOI: 10.1007/s10447-012-9152-x
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Solution-Focused Brief Therapy with a Chinese Female College Student Dealing with Relationship Loss

Abstract: Through case presentation, this article illustrates the integration of personcentered skills and guided imagery into Solution-Focused Brief Therapy (SFBT) with a Chinese female college student who was experiencing emotional distress due to relationship loss. Transcripts from select portions of actual counseling sessions further demonstrate the use of SFBT in a cross-cultural setting. The basic tenets, stages of solution building, and specific skills and techniques used in SFBT are examined in this context. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…They also stated that remembering the old and the new strategy gives the confidence to address the problem. This result is consistent with previous research conducted by Kok-Mung, Parikh, and Guo (2012), and it showed that SFBC increases the self-positive perception that helps the student to accept their problem and create a positive strategy to deal with negative emotions.…”
Section: Resultssupporting
confidence: 93%
“…They also stated that remembering the old and the new strategy gives the confidence to address the problem. This result is consistent with previous research conducted by Kok-Mung, Parikh, and Guo (2012), and it showed that SFBC increases the self-positive perception that helps the student to accept their problem and create a positive strategy to deal with negative emotions.…”
Section: Resultssupporting
confidence: 93%
“…56 This approach does not look for the pathology of the patients, but assumes them as a person who is stuck with problems. 57 Instead of an emphasis on the defects and disabilities of individuals, this approach focuses on highlighting the capabilities and successes of individuals and on creating team relations during the treatment. 58 Based on this treatment, changing and transformation is inevitable, and constructive changes are possible; therefore, in this treatment, the focus in on problems, which are likely to be changed; so, due to this, the treatment is known as hope counselling.…”
Section: Discussionmentioning
confidence: 99%
“…They also reported the process by which the content of the talk about the image of the solution during the interview can lead to a shift in the therapy sessions from the cause of the problem to a way for problem-solving. Ng, Parikh, and Guo [6] reported an SFA interview using guided imagery for a Chinese female student suffering from emotional disorders due to the experience of losing her boyfriend, and showed that the symptoms of her illness improved after three interviews. In addition, recently, SFA interviews using guided imagery have gained traction in the field of sports psychology, and have been conducted for a golf player suffering from symptoms of the yips.…”
Section: Introductionmentioning
confidence: 99%